Characterization and Development of Foot Scrub from Sarai-Bai-Ma-Kud Halimeda macroloba - Nilphet, Passawee; Phetcharat, Sinjai; Darakrai, Anuchit; Kaewtatip, Kaewta; Mayakun, Jaruwan (PKRU SciTech Journal, 2022)
Halimeda macroloba is a green seaweed containing high calcium carbonate in its segments. Moreover, H. macroloba contained protein, lipid, carbohydrate, and fiber and was rich in oxygen, carbon, and calcium. For microbial investigation, total aerobic microbial count and total combined fungi and yeasts count is less than 10 colony forming unite (CFU)/g(mL) of autoclave sterilized H. macroloba. These numbers are passed the standard requirements of International Organization of Standardization (ISO) and undesirable specific microorganisms. Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus were not found. The results showed that it has a potential to be used as a scrub in cosmetic products. This study aimed to prepare and characterize foot scrub that made from Konjac flour, chitosan, methyl paraben, cetyl alcohol, stearic acid, propylene glycol, glycerin, aquadest and then mixed with fresh and dried H. macroloba (grain size was around 63 µm). The results showed the foot scrub with dried H. macroloba contained slightly rough texture with dark green, pH = 6 and moisture 35.47±0.64 %. This formula had the highest calcium (Ca) with around 18,850±386 mg/kg compared to formula 1 (no H. macroloba added) and formula 2 (fresh H. macroloba).